Figur dan Citra: Penceritaan Ki Manteb Sudarsono Melalui Karya Foto Potret Indra Leonardi - Ardiles Akyuwen; Yusup Sigit Martyastiadi (Universitas Multimedia Nusantara, 2022)
Photos provide multiple perceptions for the viewer. This article analyzes Ki Manteb Sudarsono's photo from the perspective of semiotic relations with the storytelling relationship between the image of man, nature, God and the third meaning. This qualitative research method will investigate the semiotic relationship between the third sign and meaning in the photo. In general, visual meaning is found through the trilogy relationship between God, nature, and humans in Ki Manteb Sudarsono's photo. Researchers can conclude that the visual meaning of an image is a reflection of the relationship of human life with God and the natural surroundings. Keywords: ki manteb sudarsono; indra leonardi; photo; potrait; semiotics